2020
DOI: 10.1016/j.ajoc.2020.100859
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal methotrexate and fluocinolone acetonide implantation for Vogt-Koyanagi-Harada uveitis

Abstract: Purpose To report a case of intravitreal methotrexate treatment and fluocinolone acetonide (Retisert®) implantation in a patient with Vogt-Koyanagi-Harada syndrome (VKH). Observations A 34-year-old male was referred for worsening vision and bilateral panuveitis consistent with VKH. He was treated with prednisone, mycophenolate mofetil, prednisolone acetate eye drops, and injections of triamcinolone and adalimumab. He failed to improve with these therapies and developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Recent studies have shown the effectiveness of intravitreal drug delivery systems such as rapamycinloaded polymeric micelles and nano-liposomes of vancomycin [13,14]. Other intravitreal drug delivery methods include the use of vitamin E/poly-lactic-co-glycolic acid microspheres containing glial cell line derived neurotrophic factor (GDNF) to protect retinal ganglion cells and biodegradable polyester amide implants for diabetic macular edema and neovascular age-related macular degeneration treatment [15][16][17]. An intravitreal injection of flurbiprofen using a novel liposome aggregate platform demonstrated prolonged drug retention and reduced inflammation in ocular tissue compared to conventional liposomes [18].…”
Section: Routes Of Administration For Treating Ocular Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown the effectiveness of intravitreal drug delivery systems such as rapamycinloaded polymeric micelles and nano-liposomes of vancomycin [13,14]. Other intravitreal drug delivery methods include the use of vitamin E/poly-lactic-co-glycolic acid microspheres containing glial cell line derived neurotrophic factor (GDNF) to protect retinal ganglion cells and biodegradable polyester amide implants for diabetic macular edema and neovascular age-related macular degeneration treatment [15][16][17]. An intravitreal injection of flurbiprofen using a novel liposome aggregate platform demonstrated prolonged drug retention and reduced inflammation in ocular tissue compared to conventional liposomes [18].…”
Section: Routes Of Administration For Treating Ocular Diseasesmentioning
confidence: 99%
“…Nanoparticles form self-assembling and ordered architectures with different topologies tailored to encapsulate the guest drugs including nanospheres, nanorod assemblies [15,16], and nanocapsules. These polymers usually respond rapidly to micro-environment changes and can release guest molecules in controlled schedules, which makes them good platforms for drug-delivery carriers.…”
Section: Dispersed Nanoparticlesmentioning
confidence: 99%
“…There is a single case report which shows the efficacy of a single dose of intravitreal MTX (400 μg/0.1 mL) in a case of Vogt-Koyanagi-Harada disease (VKH) which was previously treated with oral prednisolone and mycophenolate mofetil, subcutaneous triamcinolone, and subcutaneous adalimumab. 58 The patient suffered from bilateral panuveitis and was treated with oral prednisolone, mycophenolate mofetil. Two doses of subtenon triamcinolone and subcutaneous adalimumab were also administered earlier.…”
Section: Immunosuppressantsmentioning
confidence: 99%